Effects of sodium chloride on the thermal behavior of oxalic acid dihydrate for thermal energy storage. (1st January 2017) - Han, Lipeng; Xie, Shaolei; Liu, Shang; Sun, Jinhe; Jia, Yongzhong; Jing, Yan
Highlights: Oxalic acid dihydrate as a phase change material for TES is studied. Thermophysical properties of oxalic acid dihydrate mixtures with NaCl were determined. The aim was to improve the cyclic stability of oxalic acid dihydrate. The 100 heating and cooling cycles were measured. The best sample was oxalic acid dihydrate + 9 wt% NaCl. Abstract: Oxalic acid dihydrate (OAD), which is inexpensive and has a high initial phase transition enthalpy, is a very promising phase change material. However, severe material leakage can occur owing to the large amount of steam generated when OAD is heated to melt. This behavior subsequently degrades the thermophysical properties of OAD over time, thereby hindering further application of OAD. In the present study, NaCl was introduced as an additive in OAD to reduce its melting point. Results showed that a NaCl additive content of 9 wt% was the optimal amount to reduce the phase change temperature of OAD and produce sharp endothermal and exothermal peaks without reducing the phase change enthalpy significantly. Furthermore, minimal changes in the thermophysical properties of this mixture were observed after being subjected to 100 thermal cycles. The current findings are expected to broaden the application scope of OAD for thermal energy storage.